2022
DOI: 10.3389/fmars.2022.913972
|View full text |Cite
|
Sign up to set email alerts
|

Managing Marine Growth on Historic Maritime Structures: An Assessment of Perceptions and Current Management Practices

Abstract: Maritime built heritage (e.g., historic harbors, breakwaters, etc.) is found widely along the coastlines of Europe. Due to its age and traditional construction, built heritage may represent important and largely unidentified hotspots of biodiversity in marine and coastal environments. At the same time, marine growth (e.g., seaweed, mussels, barnacles, etc.) found on these structures may provide both deteriorative and protective functions. To ensure future research focusing on the two-way interactions between m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…Specifically, these results help address some of the concerns raised by maritime practitioners in a recent survey regarding the effects of seaweed growth on built heritage assets (e.g. Baxter et al, 2022b). Furthermore, our findings imply that opportunities exist for the application of nature‐based solutions for the management and protection of historic structures in marine environments, alongside habitat provision and biodiversity conservation.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Specifically, these results help address some of the concerns raised by maritime practitioners in a recent survey regarding the effects of seaweed growth on built heritage assets (e.g. Baxter et al, 2022b). Furthermore, our findings imply that opportunities exist for the application of nature‐based solutions for the management and protection of historic structures in marine environments, alongside habitat provision and biodiversity conservation.…”
Section: Discussionmentioning
confidence: 63%
“…Traditionally, the growth of seaweed on artificial structures has been viewed negatively (e.g. Fletcher, 1988), and a recent survey of harbourmasters and other marine managers from around the UK found that seaweed growth was generally perceived to negatively impact the conservation of maritime built heritage (Baxter et al, 2022b). In particular, seaweed was thought to have a detrimental impact on the condition of mortar.…”
Section: Introductionmentioning
confidence: 99%